The relaxation effect of prolonged expiratory breathing - Komori, Teruhisa (Ment Illn, 2018)
This study was performed to confirm that autonomic nervous activity is affected by breathing speed. I hypothesized that prolonged expiratory breathing would promote parasympathetic dominance, whereas rapid breathing would promote sympathetic dominance. Ten healthy men, ages 21-28 years old, were instructed to perform prolonged expiratory breathing (6 seconds expiration, 4 seconds inspiration) after spontaneous breathing and rapid breathing (1 second expiration, 1 second inspiration) after spontaneous breathing; changes in high frequency (HF) and low frequency (LF)/HF of heart rate variability (HRV) were measured during each type of breathing. During prolonged expiratory breathing, parasympathetic nervous function was significantly activated. Conversely, during rapid breathing, parasympathetic nervous function was significantly suppressed. The HRV method assessing sympathetic and parasympathetic modulation in this study is an indirect, non-invasive method with clear limitations. The use of additional techniques should be considered to clarify the relationships between the breathing speed and the mind.